Microstructures, absorption and adhesion evolution of FeCoCr/silicone resin coatings at elevated temperature - Yuan, Dachao; Chen, Zhiyong; Cai, Changwei; Yang, Bolin; Wang, Yujie; Chen, Zhihong (Frontiers in Materials, 2023)
Heat-resistant magnetic microwave absorption coatings are vital important for the stealth safety of apparatus working at elevated temperature or electromagnetic compatibility of high density/power electronic devices. In this work, we proposed a heat-resistant coating with nanocrystalline FeCoCr micropowders as the absorbents and silicone resin as the matrix. The evolution of microstructure, absorption and adhesion of FeCoCr/silicone resin coatings were investigated after heat treatment at 400 ℃. The results show that the roughness of FeCoCr powders slightly increased due to the formation of nanoparticles, while their crystalline phase maintained body-centered cubic structure with grain size increasing from 10.8 nm to 18.1 nm after heat treatment. The saturated magnetization and coercivity of FeCoCr powders also increased after heat treatment. The adhesion of FeCoCr/silicone resin coatings exhibited sharp increase with the extension of heat treatment time, i.e., from 7.59 MPa at room temperature to 11.78 MPa after heat treatment at 400 ℃ for 10 h; this phenomenon occurred due to the condense of FeCoCr-resin interfaces. The complex permittivity of the coating was reduced after heat treatment, while the complex permeability increased; this gave rise to enhancement of microwave absorption and showed the working potential of the FeCoCr/silicone resin coatings at elevated temperature.